Ouverture officielle du colloque « Couleurs de l’architecture » - François Goven (Bulletin du Centre de Recherche du Château de Versailles, 2006)
Mr President, as you said it’s really no coincidence that we are here today to discuss the question of colour in architecture. For while Versailles, even by its scale, develops the subject’s full scope, this is an opportunity to address specific issues of doctrine that particularly interest us at the moment. Thus over these days the discussions announce and in a way demonstrate the ideas that are undertaken with the Inspector General of the Monuments Historiques before a file is submitted for the High Commission.